An automatic rice dispenser system using microcontroller - Zabidi, Azlee (2008)
A conventional rice dispenser system offers manual way of measuring the amount of rice and often provides incorrect measurements which need to be improved to satisfy the customer's requirements. Furthermore, the rice measurement is based on a cup that is suited for people in the specific country, thus the system cannot be used globally. A solution to these problems is to employ an automatic system that provides correct measurements and flexibility in setting the desired amount of rice. This paper describes an automatic rice dispenser system that allows the user to select the desired measurement, to view the current selections and to have the exact amount of rice. The system uses a microcontroller to read the user's selection, measure the amount of rice, sense the opening of the drawer and check the presence of rice left in the drawer. A conveyor attached to a motor is used to fill in the drawer with rice from the upper container. The measurement process was performed successfully by the software controlling the data transfer between the microcontroller and the interfacing circuits.